Penyemprotan Desinfektan dan Pembuatan Apotik Hidup Sebagai Langkah Preventif Pencegahan Covid-19 - Muh Fachrul Razi Badawi; Nosakros Arya (Jurnal Pengabdian Masyarakat Hasanuddin (JPMH), 2021)
Students are intellectuals who take part in learning activities within the scope of higher education and take part in the current semester. Students in pursuing the world of lectures will definitely be identical with the Tri darma college, where the tri darma of college covers research and dedication education. To complete the study, students must pass the three points, one of which is dedication. KKN (Real Work Lecture) is one of the realities of dedication. In a separate KKN there are many programs that can be given directly to the community, some are carried out in groups and some are done individually. In general, the work programs carried out by students are adjusted to the background of the majors taken by students, or some are adjusted to the needs of the surrounding community. One form of the KKN work program is spraying disinfectants and making live pharmacies, this program seeks to welcome a pandemic, where what we experience is the spread of virus covid 19 and students are asked to provide community education to fight this pandemic.